2012
DOI: 10.1111/all.12048
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase SHP2 regulates TGF‐β1 production in airway epithelia and asthmatic airway remodeling in mice

Abstract: Background Transforming growth factor (TGF)-β1 produced in airway epithelia has been suggested as a contributor to the airway remodeling observed in asthma patients. The protein tyrosine phosphatase SHP2 is a demonstrable modulator of TGF-β1 production and thus a potential regulator of airway remodeling. Objectives To define the signal event by which SHP2 regulates asthmatic responses in airway epithelial cells by using a mouse model of experimental OVA-induced airway remodeling. Methods The airways of Shp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 29 publications
5
33
0
Order By: Relevance
“…Therefore, it can be speculated that the SHP2-induced deactivation of Smad2/3 could be the consequence of direct SHP2 phosphatase-dependent dephosphorylation of c-Abl. Our results are consistent with observations that SHP2 loss from AECs promotes epithelial-mesenchymal transition and fibrotic growth (19) but differ from those showing that SHP2 overexpression positively regulates TGFb 1 -induced airway remodeling in bronchial epithelial cells (39). Although the reasons for this discrepancy are unclear, it is possible that SHP2 will have different effects on different cells as has been previously proposed (33).…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it can be speculated that the SHP2-induced deactivation of Smad2/3 could be the consequence of direct SHP2 phosphatase-dependent dephosphorylation of c-Abl. Our results are consistent with observations that SHP2 loss from AECs promotes epithelial-mesenchymal transition and fibrotic growth (19) but differ from those showing that SHP2 overexpression positively regulates TGFb 1 -induced airway remodeling in bronchial epithelial cells (39). Although the reasons for this discrepancy are unclear, it is possible that SHP2 will have different effects on different cells as has been previously proposed (33).…”
Section: Discussionsupporting
confidence: 87%
“…As inflammation and, in particular, Th17 cell differentiation and activation are regulated by cytokines released by resident and/or inflammatory cells , the expression of TGF‐β, TNF‐α, IL‐1, IL‐6, IL‐23, and IL‐33 was assessed in the different eczema types over time (Fig. A–F).…”
Section: Resultsmentioning
confidence: 99%
“…A large number of cytokines and chemokines, such as IL‐25, IL‐33, TSLP, TGF‐β, eotaxins, monocyte chemotactic proteins (MCP) and mucins, are released from airway epithelium upon allergen challenges that initiate and/or promote the asthmatic inflammation. Our recent study demonstrated that the protein tyrosine phosphatase SHP2 regulated TGF‐β1 production in airway epithelium, thereby regulating airway remodelling. Conditional shp2 gene knockdown in airway epithelia resulted in significantly attenuated airway remodelling and lung dysfunction, for example decreased inflammatory scores, collagen deposition, smooth muscle hyperplasia and AHR.…”
Section: Basic Science Researchmentioning
confidence: 99%